VALIDASI METODE ANALISIS SIBUTRAMIN HCL PADA SEDIAAN JAMU PELANGSING DENGAN SPEKTROFOTOMETER UV-VISIBLE - Febriani, Yuyun; Izati Savitri, Nurul; Azim, Muhlisun (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2024)
Sibutramine HCl was known as one of the anti-obesity drugs known for its appetite-suppressing properties. The aims of this research were to analyze pharmaceutical chemicals content in slimming herbal remedies available in the East Lombok district market and to analyze the value and validation parameters for analyzing method of sibutramine HCl in these remedies using UV-Visible spectrofotometry. The method used qualitative analysis using thin-layer chromatography (TLC) and quantitative method used spectrophotometry UV-Visible. The method was validated to meet the specified requirements, including linearity, Limit of Detection (LoD), Limit of Quantification (LoQ), precision, and accuracy. The results of this research were, in qualitative analysis, 2 out of 5 samples were identified to contain sibutramine HCl with a value of Rf of 0.78. The selected wavelength for sibutramine HCl analysis was 224.40 nm, and the respective parameters of linearity, LoD, LoQ, precision, and accuracy were (r) 0.9991, 2,406 ppm, 7,291 ppm, 0.446% RSD, and 98.92% recovery. Based on the results above, showed that using the spectrofotometry UV-Visible method in this research complies with the established parameters.